Transitioning experiences of internationally educated nurses in host countries: A narrative systematic review - Aasia Rajpoot; Clair Merriman; Anne-Marie Rafferty; Catherine Henshall (Elsevier, 2024)
Background: The shortage of nurses worldwide is a well-known issue that has changed the health and social workforce picture. Increased recruitment and migration of internationally educated nurses in the health and social care workforce pose many risks to successful integration into the healthcare system. Understanding the barriers and enablers affecting their integration in their host countries is imperative. Objective: To critically and systematically review the current literature to explore the transitioning experiences of internationally educated nurses to understand the enabling influences affecting their workforce integration into their host countries. Design: A narrative systematic literature review was conducted. This study was registered in the International Prospective Register of Systematic Reviews (Registered Number: CRD42023401090). The study results were reported as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Methods: A comprehensive literature search using the search engines CINAHL, MEDLINE, PsycINFO, Academic Search, and PubMed was conducted. Only peer-reviewed papers written in the English language were included. Primary research studies published between 2019 and 2023, which explored the lived experiences of internationally educated nurses, were considered for review. Results: Seventeen studies (16 qualitative and one quantitative) were included in the review. Three main themes were developed: (1) push and pull factors that mediated internationally educated nurses' migration experiences, (2) one-way integration logic, and (3) expectations versus reality. Conclusions: There is a need for a comprehensive and collaborative organisational approach to enhance the integration experiences of internationally educated nurses into their host countries. This can also ensure their contribution is recognised and will help them fulfil the responsibilities of their role and become influential team members within their organisations. This comprehensive and collaborative approach is also required to tackle discrimination, racism, communication and language barriers. Addressing these challenges can improve internationally educated nurses' job satisfaction and, thereby, improve retention. Tweetable abstract: A new systematic review study explores barriers and enablers for optimising internationally educated nurses' experiences of working in their host country @cathy_Henshall @clairmerriman9 @annemarieraffer